Antibacterial Carbon‐Based Nanomaterials. Issue 45 (31st October 2018) - Xin, Qi; Shah, Hameed; Nawaz, Asmat; Xie, Wenjing; Akram, Muhammad Zain; Batool, Aisha; Tian, Liangqiu; Jan, Saad Ullah; Boddula, Rajender; Guo, Beidou; Liu, Qian; Gong, Jian Ru
Abstract: The emergence and global spread of bacterial resistance to currently available antibiotics underscore the urgent need for new alternative antibacterial agents. Recent studies on the application of nanomaterials as antibacterial agents have demonstrated their great potential for management of infectious diseases. Among these antibacterial nanomaterials, carbon‐based nanomaterials (CNMs) have attracted much attention due to their unique physicochemical properties and relatively higher biosafety. Here, a comprehensive review of the recent research progress on antibacterial CNMs is provided, starting with a brief description of the different kinds of CNMs with respect to their physicochemical characteristics. Then, a detailed introduction to the various mechanisms underlying antibacterial activity in these materials is given, including physical/mechanical damage, oxidative stress, photothermal/photocatalytic effect, lipid extraction, inhibition of bacterial metabolism, isolation by wrapping, and the synergistic effect when CNMs are used in combination with other antibacterial materials, followed by a summary of the influence of the physicochemical properties of CNMs on their antibacterial activity. Finally, the current challenges and an outlook for the development of more effective and safer antibacterial CNMs are discussed. Abstract : The recent research progress on antibacterial carbon‐based nanomaterials (CNMs) is reviewed, first focusing on the physicochemical parameters of CNMs, then introducing various antibacterial mechanisms and discussing the influence of physicochemical parameters on their antibacterial activity. Finally a conclusion is presented highlighting the current challenges and future perspectives for the development of more effective and safer antibacterial CNMs.